Troubadour blues - Weber, Tom (Thomas J.); Case, Peter, 1954-; Smither, Chris; Gauthier, Mary; Tom Weber Films; Soundview Media Partners ([Erie, Pa.] : Tom Weber Films LLC, 2011)
Documentary on traveling singer-songwriters keeping alive the tradition of the itinerant bluesmen and folksingers who hopped freight trains and hitched rides across Depression-era America.
Troubadour Blues is a journey into the world of well-traveled singer-songwriters like Peter Case, Mary Gauthier, Chris Smither, Dave Alvin, Slaid Cleaves and many more. This 95-minute documentary, produced over a 10-year period by filmmaker Tom Weber, provides a revealing look at the heartbreaks and joys of these modern-day wandering minstrels. The film contains live performances of 40 brilliantly crafted songs, as well as informal moments and interviews in which the artists reflect on audiences, songwriting, the music business, and life. This is a story that needs to be heard. In our media-saturated age of instant pop stardom, there is real danger that the tradition of the itinerant working musician is being diluted or lost. This is a concern expressed in the film by a number of artists. Troubadour Blues explores the hidden corners of our culture, where honest, authentic songs reflecting the human experience are still being composed and sung.
Originally released as a motion picture in 2011.
Peter Case, Chris Smither, Mary Gauthier, Dave Alvin.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2019)
Keywords: Singers -- United States; Composers -- United States; Folk music -- United States; Country music -- United States; Documentary films; Nonfiction films; Internet videos; Streaming video